An accelerated algorithm for calculating the secondary structure of single stranded RNAs. - Comay, E (1984)
We describe a code designed for secondary structure computation of single stranded RNA molecules. While it incorporates the same principles as the original algorithm of Nussinov et al (1978), its restructuring improves the logic and the approach of the codes based on it. For long sequences the code is at least an order of magnitude faster. For a chain n nucleotides long, references to computer disk memory are reduced from n3 to less than n2. For n much greater than 100, disk references behave like n3/6000.